THE INCREASING OF SELF-CONCEPT THROUGH RET ON SUBJECT ID: AS A VICTIM OF DRUG ABUSED AT JAYAGIRI VILLAGE, LEMBANG SUB-DISTRICT, BANDUNG BARAT REGENCY - Anandri Novan Pratama; Admiral Nelson Aritonang; Epi Supiadi (Politeknik Kesejahteraan Sosial Bandung, 2019)
This study aims to examine the effect of Rational Emotive Therapy (RET) on the improvement of self-concept in the subject ID of victims of drug users. Perceptions reflected in the subject's internal and external behaviors that lead to the disruption of their self-concept are the focus of the intervention in this study. The research approach used is quantitative research using Single Subject Design (SSD) or N = 1. The research model used is A-B-A which occurs from three phases, among others, Phase A1 (baseline), Phase B (Intervention), and phase A2 (results). The instrument used is a questionnaire developed by researchers based on the theory of William H. Fitts. Data collection techniques used are in-depth interviews, questionnaires, and documentation studies. The data obtained was analyzed by charting and making descriptive statistics. The results showed that the application of Rational Emotive Therapy (RET) succeeded in improving self-concept which previously made subjects not adaptive to the environment. Changes that occur after subject therapy experience an increase in self-concept shown by the reduction of irrational thoughts and subjects become more adaptive to their environment. This research recommendation can be continued to look at the effect of RET therapy in handling the problems of self-concept of victims of drug users in the future and can contribute ideas in the development of social work science in dealing with drugs.